Ectopic testis: an experience of a tertiary-level urology center at Upper Egypt - Rabea Ahmed Gadelkareem; Ahmed Abdelhamid Shahat; Ahmed Reda; Ahmed Mohamed Moeen; Mohamed Farouk Abdelhafez; Mahmoud Farouk Abughanima; Osama Mansour; Nasreldin Mohammed; Mahmoud Mohammed Osman; Ahmed Abdelaziz Elderwy; Hisham Mokhtar Hammouda (Annals of Pediatric Surgery, 2020)
Abstract Background Testicular ectopia is defined as a testis which is located away from the normal pathway of testicular descent and outside its ipsilateral hemiscrotum. Controversies have been raised about considering the abdominal and inguinal ectopic testes as undescended ones. Our purpose was to review our center’s experience with the diagnosis and management of testicular ectopia focusing on the inguinal ectopic testis. Retrospectively, we studied the clinical and surgical characteristics of a case series of testicular ectopia which was managed in our center during July 2001–June 2016. Results Out of 1132 patients with undescended testes, 44 cases (3.9%) had testicular ectopia. Twenty-three cases (mean age = 5.15 ± 5.79 years) fulfilled the criteria of inguinal ectopic testis. Clinically, testes were relatively mobile and superficial. Surgically, they were located in the superficial inguinal pouch, had relatively long spermatic cords, and commonly had average rather than small sizes. The other ectopic 21 cases (mean age = 10.56 ± 6.92 years) were perineal, anterior abdominal wall, femoral, prepubic, and transverse testes in 7 (33.3%), 4 (19%), 4 (19%), 3 (14.3%), and 3 (14.3%) cases, respectively. Congenital inguinal hernia was the commonest associated anomaly (22.7%). All cases were treated surgically with only 1 case of testicular atrophy (2.3%). Conclusions Testicular ectopia is rare with relatively delayed presentations. Different anatomical sites have been reported including the superficial inguinal pouch and anterior abdominal wall with variable complexities and controversies. The inguinal ectopic testis is the most controversial, but it might be characterized from other entities based on certain clinical and surgical criteria.